2020
DOI: 10.1158/1055-9965.epi-18-1123
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Personalized Screening for Colorectal Cancer Based on Polygenic Risk and Family History

Abstract: Background: There is growing evidence for personalising colorectal cancer (CRC) screening based on risk factors. We compared the cost-effectiveness of personalised CRC screening based on polygenic risk and family history to uniform screening.Methods: Using the MISCAN-Colon model, we simulated a cohort of 100 million 40-year-olds, offering them uniform or personalised screening. Individuals were categorised based on polygenic risk and family history of CRC. We varied screening strategies by start age, interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 51 publications
1
51
0
Order By: Relevance
“…However, we have shown that these benefits of risk-stratification diminish if resources are available to screen the entire population at a younger age. This result is supported by evidence from other modelling studies that have compared strategies in which screening starts from age 50 or younger, and which have concluded that risk stratification based on genetic risk is not likely to be more cost-effective than uniform screening at current levels of risk score discrimination (13,14). This means that whilst riskstratification may be an attractive option currently in England where population screening starts at age 60, it may not be attractive in other countries that start screening at lower ages, or in England in the future if more resources become available for screening.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, we have shown that these benefits of risk-stratification diminish if resources are available to screen the entire population at a younger age. This result is supported by evidence from other modelling studies that have compared strategies in which screening starts from age 50 or younger, and which have concluded that risk stratification based on genetic risk is not likely to be more cost-effective than uniform screening at current levels of risk score discrimination (13,14). This means that whilst riskstratification may be an attractive option currently in England where population screening starts at age 60, it may not be attractive in other countries that start screening at lower ages, or in England in the future if more resources become available for screening.…”
Section: Discussionsupporting
confidence: 61%
“…on May 30, 2021. © 2021 American Association for cancerpreventionresearch.aacrjournals.org Downloaded from Whilst risk-based screening has not been evaluated in clinical trials, several recent modelling studies have examined the potential cost-effectiveness of risk-based strategies (13)(14)(15). However, these analyses have several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] There are also examples of CEAs that consider multiple risk strata together in a single analysis, meaning the variation of eligibility between risk strata is combined with variation of screening intensity when specifying alternative screening strategies. [11][12][13][14][15][16][17][18][19] The problem addressed by this study is the notable variation of methods used within the risk-stratified cancer-screening CEA literature and the attendant likelihood that present analyses might not necessarily provide policy makers with optimal policies. This problem primarily relates to analyses within the latter group of studies identified above-those that use variation in the eligibility criteria as part of the definition of alternative screening strategies.…”
Section: Introductionmentioning
confidence: 99%
“…17 Two examples of applied studies that have considered a wide variety of screening strategies are Vilaprinyo et al's analysis of breast screening strategies for 4 risk strata combined in 1 analysis and Cenin et al's analysis of alternative colorectal cancer screening intensity based on polygenic and familial risk. 11,18 Although not documented within the studies, it appears both have identified the overall optimal frontier by determining the withinstrata frontiers and then combined them. These 2 examples could be interpreted as resembling approach 5.…”
mentioning
confidence: 99%
“…E cacy of systemic treatments depends on geography, race, age, and other clinicopathological features (12). Personalized regimen would be required for better therapeutic effect on individual, which should be guided by a comprehensive prognostic model to predict possible survival outcomes under given circumstances (13). By far, no such predictive model for CRC patients was constructed.…”
Section: Introductionmentioning
confidence: 99%